Nitrogen and Phosphorus interactions in plants: from agronomic to physiological and molecular insights. (October 2020) - Krouk, Gabriel; Kiba, Takatoshi
Abstract : Nitrogen (N) and Phosphorus (P) are the two most essential nutrients ensuring food production and security. The ever growing population demands more N and P-based fertilizers. Even though the N provision to the agricultural system is virtually infinite (Haber and Bosch process) it triggers pollution when it is not used by the plant and leaks into the environment. On the other hand, P is predicted to be a limited source worldwide. P use is also responsible for water eutrophication. Thus understanding plant response to combinations of N and P has clear implications for sustainable human development. Recent works have shed new light on how N and P closely interact to control plant responses. Several molecular actors have been revealed controlling the molecular interaction between these two essential elements drafting a working model of N and P interactions. We summarize here these new findings as well as several previous lines of evidence in agronomy and physiology studies preceding this new trend of investigation in the molecular world.